1996
DOI: 10.1111/j.1440-1827.1996.tb03613.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal primitive neuroectodermal tumor: An immunohistochemical and cytogenetic analysis

Abstract: The cytogenetic and morphologic characteristics of a case with a primitive neuroectodermal tumor (PNET) arising from the left kidney in a 22 year old man are presented. The patient was detected as having a left renal mass with a tumor embolus in the inferior vena cava and multiple pulmonary metastases. A radical nephrectomy with tumor embolectomy of the inferior vena cava, along with a resection of the pulmonary nodules were performed. Histologic examination revealed a dense proliferation of small round cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Renal PNET is positive for CD99 in more than 90-95% of the cases [5]. Other helpful markers are neuron-specific enolase and vimentin, synaptophysin and S100 protein [4,15]. Furthermore, cytogenetic studies showed that renal PNET is consistently associated with translocation of the long arms of chromosome 11 and 22, t(11:22) (q24:q12) in more than 90% of the tumors, it is also characteristic of PNET and Ewing's sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Renal PNET is positive for CD99 in more than 90-95% of the cases [5]. Other helpful markers are neuron-specific enolase and vimentin, synaptophysin and S100 protein [4,15]. Furthermore, cytogenetic studies showed that renal PNET is consistently associated with translocation of the long arms of chromosome 11 and 22, t(11:22) (q24:q12) in more than 90% of the tumors, it is also characteristic of PNET and Ewing's sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…3B), which recognizes a cell membrane protein that is the product of MIC2 (p30-32 MIC2 ) [9,10]. To a minor extent but always positive were the reactions for the antibodies directed to neuron-specific enolase, Leu-7, and vimentin.…”
Section: Abdominal Imagingmentioning
confidence: 99%
“…Neuronal differentiation was observed in six of eight cases, and nine died. None of these reports documented a positive PAS reaction and CD99 (MIC 2), the characteristics of peripheral PNET, 10,11 or the cytologic findings. In 1971, Rubinstein outlined the concept of PNETs.…”
Section: A B Cmentioning
confidence: 98%
“…Immunohisto- chemically, the tumor cells weakly expressed CD99 (MIC-2) ( Figure 5). 10,11 In addition, the cells stained for several neural markers, with an especially strong positive reaction for NSE and synaptophysin and a weak reaction for GFAP. Neurofilament and S-100 protein were negative, but other neural markers, including chromogranin A, were positive in the tumor cells ( Figure 5).…”
Section: Immunoperoxidase Examinationmentioning
confidence: 99%